Integrated processing of agricultural raw materials using biotechnological baromembrane and ultrasonic methods - Sattarov Narmurod; Fazilov Dusmurat; Ulashov Jonibek; Radjapova Natalya; Mamatkulova Shakhnoza; Kuznetsova Yu.S. (BIO Web of Conferences)
A comprehensive approach to the creation of a universal industrial line for the production of food and feed ingredients from various agricultural raw materials based on the integration of biotechnological, baromembrane and ultrasonic methods is presented. The research included the development of methods of directed enzymatic catalysis intensified by ultrasonic influence, as well as modern technologies of membrane concentration and purification. It was experimentally established that the use of an integrated approach allows to significantly increase the yield of target components from plant and secondary raw materials, such as proteins, amino acids, vitamins, pectin substances. In particular, at processing of grain bard the protein content in dry matter increased up to 40-45%, and at processing of beet pulp the yield of pectin substances increased by 20-25%. Ultrasonic treatment reduced extraction time by 10-15% and enzyme consumption by 5-10%. The results obtained demonstrate the prospects of this approach for the creation of environmentally friendly and resource-saving production of food and feed ingredients.